Enhancement of carbon sequestration of MgO-based concrete - Yeo, Hui Xian (Nanyang Technological University, 2021)
In a highly populated country in Singapore, it is inevitable to find buildings constructed using concrete thus we cannot ignore the environmental impacts that results from the manufacturing of cement to produce concrete. One of the environmental issues that arises from the manufacturing of cement is the carbon dioxide (CO2) gas into the atmosphere which causes global warming and increased occurrence of flooding. Among the possible alternative binders to Ordinary Portland Cement (OPC), reactive magnesium oxide (MgO) cement is considered more sustainable since it results in lesser net CO2 emissions. In this project, the aim is to reduce CO2 emissions through the enhancement of carbonation in MgO based cement. This will be carried out using microbial methods and the design of MgO-based pervious concrete. For microbial approach, the effect of the carbonic anhydrase (CA)-producing bacterial on the mechanical performance and carbon sequestration of MgO-based concrete was investigated. It was found that CA-producing bacteria led to the highest percentage increase in compressive strength and carbon sequestration at 89.8% and 84%, respectively. Furthermore, the MgO-based pervious concrete with different void ratios was studied. Samples with a void ratio of 0.25 showed a 7-day compressive strength of 26.3 MPa, which meets its functionality. Moreover, wet/dry cycles had a positive effect on the strength gain and carbon sequestration in MgO-based pervious concrete.